Ultrasound and laser-promoted dual-gas nano-generator for combined photothermal and immune tumor therapy - Li, XinYu; Gao, Yong; Liu, XinZheng; Hu, XiaoQian; Li, YunMeng; Sun, JunXi; Wang, PingYu; Wu, Hongkai; Kim, HaeWon; Ramalingam, Murugan; Xie, ShuYang; Wang, RanRan (Frontiers in Bioengineering and Biotechnology, 2022)
The combination of photothermal therapy (PTT) and immune tumor therapy has emerged as a promising avenue for cancer treatment. However, the insufficient immune response caused by inefficient immunogenic cell death (ICD) inducers and thermal resistance, immunosuppression, and immune escape resulting from the hypoxic microenvironment of solid tumors severely limit its efficacy. Herein, we report an ultrasound and laser-promoted dual-gas nano-generator (calcium carbonate-polydopamine-manganese oxide nanoparticles, CPM NPs) for enhanced photothermal/immune tumor therapy through reprogramming tumor hypoxic microenvironment. In this system, CPM NPs undergo reactive decomposition in a moderately acidic tumor, resulting in the generation of calcium, manganese ions, carbon dioxide (CO2), and oxygen (O2). Calcium and manganese ions act as adjuvants that trigger an immune response. The cancer cell membrane rupture caused by sudden burst of bubbles (CO2 and O2) under ultrasound stimulation and the photothermal properties of PDA also contributed to the ICD effect. The generation of O2 alleviates tumor hypoxia and thus reduces hypoxia-induced heat resistance and immunosuppressive effects, thereby improving the therapeutic efficacy of combination PTT and immune therapy. The present study provides a novel approach for the fabrication of a safe and effective tumor treatment platform for future clinical applications.